Self‐compassion and savouring buffer the impact of the first year of the COVID‐19 on PhD students' mental health. (20th March 2022) - Paucsik, Marine; Leys, Christophe; Marais, Gabriel; Baeyens, Céline; Shankland, Rebecca
Abstract: Doctoral students face many challenges that were reinforced by COVID‐19‐related lockdowns. We assessed this impact over 1 year on doctoral students' depression, anxiety, stress, well‐being, and doctoral engagement. We also investigated the potential protective role of self‐compassion and savouring on mental health, well‐being, and doctoral engagement. A total of 134 PhD students from several French universities responded to the three‐time points of this longitudinal study. The results showed a significant increase in depression, anxiety and stress and a significant decrease in well‐being and doctoral engagement during the first year of the pandemic. Self‐compassion and savouring predicted lower levels of depression, anxiety, and stress, and higher levels of well‐being over time. Savouring alone predicted higher doctoral engagement over time. This study reveals the significant impact of the pandemic year on the mental health of doctoral students, and the relevance of self‐compassion and savouring as psychological resources to cope with adversity.